TEODISASTER DAN MITOLOGI CILIWUNG Case Study Satria dan Bintang di Taman Pingkal - Suhardin, Suhardin; Hunen, Ahmad; Erwina, Erwina (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The objective research, examine the cases of the sinking of Satria Rivano and Bintang Putra Erfansah in the perspective of teodisaster, correct understanding related to sincerity in accepting disaster as a provision and will of Allah SWT as a manifestation of Allah SWT's love and justice, rectify erroneous understandings related to mystical, nature goes according to role Allah. The method used is case study with the steps of selecting topics, reviewing literature, collecting data, processing data and drawing conclusions based on data and studies. The findings obtained in this study, that the drowning of the two children was purely a disaster given by Allah SWT as a form of His love for all parties to learn from this incident, improve themselves to be better in the future. All parties carry out introspection, study and self-evaluate, honestly, transparently, objectively and ask Allah's forgiveness, for all self-deficiencies.